Cross diagnostics measurements of heat load profiles on the lower tungsten divertor of WEST in L-mode experiments - N. Fedorczak; J. Gaspar; Y. Corre; A. Grosjean; X. Courtois; J.P. Gunn; R. Mitteau; R. Dejarnac; J. Bucalossi; E. Tsitrone; T. Loarer; S. Brezinsek (Nuclear Materials and Energy, 2021)
WEST is a full metallic tokamak with an extensive set of diagnostics for heat load measurements. In this paper, heat loads on the lower divertor of WEST are investigated using two independent methods. A first method relies on the thermal inversion of temperature measurements from arrays of thermal sensors embedded a few millimeters below the surface, while the second consists in the inversion of black body surface temperatures measured by infra-red (IR) thermography. The challenge of IR based temperature measurements in the full metal environment of WEST is addressed through a simplified model, allowing to correct for global reflections and low surface emissivities of tungsten surfaces. A large database (>100L-mode discharges) is investigated. It is found that the energy absorbed by an outer divertor tile during a plasma discharge is closely estimated by the two diagnostics, over a large set of experimental conditions. A similar match is also found for the peak heat flux value on the outer target. The toroidal modulation of target heat loads by magnetic ripple is found to be consistent with the geometrical projection of a parallel heat flux component. Additionally, the heat flux channel width at the target is found to scale linearly with the magnetic flux expansion as expected. These observations give confidence in the robustness of the data from both diagnostics, and confirm the simple geometrical rules at use in the description of heat flux deposition on divertor targets. However, it is shown that the heat flux channel width estimated from infra-red thermography is about three times lower than the width estimated from embedded measurements, which is still under investigation.